The lived experiences of rural women diagnosed with the human immunodeficiency virus in the antenatal period - Genevieve Marion Fords; Talitha Crowley; Anita S van der Merwe (SAHARA-J, 2017)
Background: In South Africa, pregnant women are diagnosed with human immunodeficiency virus (HIV) at antenatal clinics and simultaneously initiated on antiretroviral treatment (ART). An HIV diagnosis together with the initiation of ART has an emotional impact that may influence how pregnant women cope with pregnancy and their adherence to a treatment plan. The aim of the study was to explore the lived experiences of women diagnosed with HIV in the antenatal period in a rural area in the Eastern Cape province of South Africa. Methods: A qualitative approach with a descriptive phenomenological design was utilised. The study applied purposive sampling to select participants from a local community clinic in the Eastern Cape. Ten semistructured interviews were conducted, transcribed and analysed using Colaizzi's framework. Results: Four themes formed the essential structure of the phenomenon being investigated: a reality that hits raw, a loneliness that hurts, hope for a fractured tomorrow and support of a few. Although the participants had to accept the harsh reality of being diagnosed with HIV and experienced loneliness and the support of only a few people, they had hope to live and see the future of their children. Conclusion: Women diagnosed with HIV during pregnancy are ultimately concerned with the well-being of their unborn children, and this concern motivates their adherence to ART. Women's lived experiences are situated in their unique sociocultural context, and although some known challenges remain, counselling and support strategies need to be informed by exploring context-specific issues and involving the local community.